2002
DOI: 10.1002/jmv.10239
|View full text |Cite
|
Sign up to set email alerts
|

Viral genotypes and response to interferon in patients with acute prolonged hepatitis B virus infection of adulthood in Japan

Abstract: Acute hepatitis B virus (HBV) infection was diagnosed in 57 adults admitted to Toranomon Hospital in Tokyo, Japan. Genotypes of HBV were determined by a serological method and compared to those in 1,077 patients with chronic hepatitis B. The distribution of genotypes were: genotype A (acute, 22.8% vs. chronic, 1.9%; P < 0.00001); B (14.0% vs. 9.4%); C (43.9% vs. 87.7%, P = 0.004); D (1.8% vs. 0.2%); F (1.8% vs. 0.2%); and unable to be typed (15.8% vs. 0.6%, P = 0.001). The infection persisted in seven (12%) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
52
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 33 publications
(47 reference statements)
4
52
1
Order By: Relevance
“…There is growing evidence that HBV genotypes may influence the outcomes and the severity of HBV, mainly in Asian studies, with more serious disease observed in patients infected with genotype C (Lindh et al 1999, Kao et al 2000, Kobayashi et al 2002, Sakugawa et al 2002, Sugauchi et al 2002, Wai et al 2002, Chan et al 2003, Lee et al 2003, Nakayoshi et al 2003, Sumi et al 2003. Nevertheless, the informations about differences in the clinical, virological and histological characteristics among patients with genotypes non-B and non-C, prevailing in Western countries, are scarce and controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that HBV genotypes may influence the outcomes and the severity of HBV, mainly in Asian studies, with more serious disease observed in patients infected with genotype C (Lindh et al 1999, Kao et al 2000, Kobayashi et al 2002, Sakugawa et al 2002, Sugauchi et al 2002, Wai et al 2002, Chan et al 2003, Lee et al 2003, Nakayoshi et al 2003, Sumi et al 2003. Nevertheless, the informations about differences in the clinical, virological and histological characteristics among patients with genotypes non-B and non-C, prevailing in Western countries, are scarce and controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the information on the clinical significance of HBV genotypes has been based on studies from Asia countries and is restricted to comparisons between genotypes B and C (Lindh et al 1999, Kao et al 2002, Kobayashi et al 2002, Sakugawa et al 2002, Wai et al 2002, Lee et al 2003, Nakayoshi et al 2003, Sumi et al 2003. Few studies have evaluated the role of genotypes in non-Asian population and the infection outcomes (Mayerat et al 1999, Sanchez-Tapias et al 2002, Thakur et al 2002, Chu et al 2003, Gandhe et al 2003, Kumar et al 2005, Halfon et al 2006, Madan et al 2009).…”
mentioning
confidence: 99%
“…The infectious routes of blood transfusion, non-sterilized medical materials, and maternal transmission are well controlled now, however, sexual transmission, which is the most common infectious route for adults in Japan [Arima et al, 2003], remains uncontrolled. On the other hand, several reports from the metropolitan area in Japan have described that acute hepatitis with HBV/A infection due to sexual transmission has been increasing [Kobayashi et al, 2002;Ogawa et al, 2002]. Those reports together with the present study led to the suspicion that HBV/A and HBV/D, whose main infectious routes are horizontal, might become the dominant genotypes in Japan in the future, rather than HBV/B and HBV/C, whose main infectious route is vertical, if a suitable preventive policy for HBV transmission is not established.…”
Section: Discussionmentioning
confidence: 99%
“…During 31 years, 128 patients with genotype A visited there. Unlike most infections with genotype B and C transmitted perinatally from carrier mothers with HBeAg [Okada et al, 1976], genotype A infection in Japan is often acquired in the adulthood by men having extramarital sexual contacts either with men or women; there has been no evidence for maternal transmission of HBV genotype A in Japan [Kobayashi et al, 2002Ogawa et al, 2002;Suzuki et al, 2005]. HBV infection prevails among homosexuals in Western countries where genotype A is frequent, who poorly respond to vaccines [Goilav and Piot, 1989].…”
Section: Discussionmentioning
confidence: 99%
“…HBV infection prevails among homosexuals in Western countries where genotype A is frequent, who poorly respond to vaccines [Goilav and Piot, 1989]. Genotype A infection in Japan has a propensity to become chronic and tends to respond to antiviral therapies better than genotype B or C infection [Kobayashi et al, 2002, 2003Suzuki et al, 2005.…”
Section: Discussionmentioning
confidence: 99%